Minimal processing of honey pamelo (Citrus grandis (L.) osbeck) - Sabrina, Anak Lawrence Anyau. (Universiti Malaysia Sarawak (UNIMAS), 2006)
Minimal processing of honey pomelo was carried out. The fruits were peeled and the segments make up with edible juice sacs were placed in a plastic container (polypropylene container) and the samples were stored at three temperatures i.e 5°C, 10°C and ambient. In the first experiment, samples were analyzed for Brix, pH, total soluble solids, acidity and vitamin C at day 0, 3, 6, 8 and 12. In the second experiment, the samples were analyzed for the same parameters at day 0, 2, 4, 6 and 8. Statistical analysis of the first experiment showed that storage temperatures did not affect quality parameters for up to 6 days significantly. After 8 days or longer, changes in quality parameters due to storage temperatures were significant. In the second experiment, quality parameters of minimally processed honey pomelo did not change significantly when stored at 5°C, 10°C for 8 days in storage. Result of this study showed that minimally processed honey pomelo can last for up to 8 days or longer when stored at 5°C and 10°C. The ambient samples could only be stored for not more than 6 days.